Biofilm in Genital Ecosystem: A Potential Risk Factor for Chlamydia trachomatis Infection - Simone Filardo; Marisa Di Pietro; Giulia Tranquilli; Rosa Sessa (Canadian Journal of Infectious Diseases and Medical Microbiology)
In healthy women, the cervicovaginal microbiota is mostly populated by Lactobacillus spp., the main host defense factor of the female genital tract. In addition to Lactobacilli, other microorganisms populate the cervicovaginal microbiota, like Candida spp. and Gardnerella vaginalis. The overgrowth of Candida spp. or G. vaginalis, known as biofilm-producing microorganisms in the genital ecosystem, may lead to microbial dysbiosis that increases the risk of acquiring sexually transmitted infections, like Chlamydia trachomatis. C. trachomatis, the leading cause of bacterial sexually transmitted diseases, is still considered an important public health problem worldwide because of the impact of asymptomatic infections on long-term reproductive sequelae, including pelvic inflammatory disease and infertility. The aim of our study was to investigate the interaction between C. trachomatis and the biofilm produced by Candida albicans or Gardnerella vaginalis, evaluating whether the biofilm can harbor C. trachomatis and influence its survival as well as its infectious properties. In order to do so, we developed an in vitro coculture transwell-based biofilm model. Our findings proved, for the first time, that C. trachomatis, an intracellular obligate pathogen, survived, for up to 72 hours after exposure, inside the biofilm produced by C. albicans or G. vaginalis, retaining its infectious properties, as evidenced by the typical chlamydial inclusions observed in the cell monolayer (chlamydial inclusion-forming units at 72 h: 9255 ± 1139 and 9873 ± 1015, respectively). In conclusion, our results suggest that the biofilm related to Candida or Gardnerella genital infections may act as a reservoir of C. trachomatis and, thus, contribute to the transmission of the infection in the population as well as to its dissemination into the upper genital tract, increasing the risk of developing severe reproductive sequelae.